2021
DOI: 10.1021/acs.orglett.1c00617
|View full text |Cite
|
Sign up to set email alerts
|

Borylation of Unactivated C(sp3)–H Bonds with Bromide as a Traceless Directing Group

Abstract: A palladium-catalyzed alkyl C−H borylation with bromide as a traceless directing group is described, providing a convenient approach to access alkyl boronates bearing a β-allcarbon quaternary stereocenter. The protocol features a broad substrate scope, excellent site selectivity, and good functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…On the basis of both our aforementioned results and previous studies reported in the literature, [2][3][4][5][6][7][8][9][10][11] we proposed a mechanism for the palladium-catalyzed C(sp 3 )-H activation coupling reaction proceeding by a 1,4-Pd shift (Scheme 6). Initially, the Pd (0) catalyst coordinates to substrate 1a providing intermediate A, which undergoes oxidative addition to generate Pd(II) intermediate B.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…On the basis of both our aforementioned results and previous studies reported in the literature, [2][3][4][5][6][7][8][9][10][11] we proposed a mechanism for the palladium-catalyzed C(sp 3 )-H activation coupling reaction proceeding by a 1,4-Pd shift (Scheme 6). Initially, the Pd (0) catalyst coordinates to substrate 1a providing intermediate A, which undergoes oxidative addition to generate Pd(II) intermediate B.…”
Section: Resultssupporting
confidence: 62%
“…In the past two decades, palladium-catalyzed activation of remote C(sp 3 )-H has emerged as a powerful method for the construction of a variety of C-C bonds, 1 most of which rely on the deployment of the 1,4-palladium shift strategy. 2,[5][6][7][8][9][10][11] As can be seen in Scheme 1, the in situ-generated diorganopalladacycle A via oxidative addition of Pd(0) to a C(sp 2 )-X bond and further cleavage of the proximate intramolecular C(sp 3 )-H bond leads to potential transformations. Alternatively, the ring-opening of palladacycle A through protonation or oxidative addition/reductive elimination provides an σ-alkylpalladium complex B, hence resulting in an overall 1,4-palladium shift as initially observed by Dyker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 2 Gram-scale preparation Based on the above experimental results and previous reports, [13][14]17] a tentative catalytic cycle is proposed as shown in Scheme 3. The initial oxidative addition of aryl bromide 1a to palladium(0) generates the intermediate A.…”
Section: Resultsmentioning
confidence: 92%
“…Visible light catalysis 5 has become a well-accepted and powerful method for the direct borylation of drug like molecules. Seminal studies by Larionov, 6 Aggarwal, 7 Wu, 8 Schelter 9 and others 10 have established the viability and synthetic utility of this approach, circumventing the need for well recognized photocatalysts and metal additives. Studer 11 developed radical borylation of aryl iodides with bis(catecholato)diboron (B 2 cat 2 ) as the boron source under mild conditions.…”
Section: Introductionmentioning
confidence: 99%